Evaluation of Reactive Oxygen Species, Antioxidants and Lipid Peroxidation Biomarkers in Diabetics Mellitus Type2 - Abdul Hussein Jabbar, Amer Radhi; ali kamil, Tabarek; Mohammed Khadairi, Maher (Clinical Medicine And Health Research Journal, 2024)
This study aims to evaluate the reactive oxygen species ROS, enzyme and non-enzyme antioxidants and peroxidation of lipid biomarkers in diabetic patients in diabetic center of Merjan hospital city. The current study reveals that the concentration of reactive oxygen species, Malondialdehyde MDA, catalase CAT and glutathione S-transferase activities were appeared significant differences at P≤ 0.05 that increased in diabetic disorder when compared with patient without diabetic While the activity of superoxide dismutase, concentration of vitamin C and glutathione were revealed significant differences at P ≤ 0.05 which are decreased in patients when compare with healthy volunteers .